Mobile AMOLED Display Power Model Considering I-R Drop in Smartphones - Lim, Seong Geun; Lee, Keetark; Kim, Young Jin (IEEE Transactions on Industrial Electronics, 2021)
In order to efficiently manage display power, there is a need for a system that can accurately predict the power consumed according to the displayed image. Existing AMOLED display power models do not consider the effects of I-R drop, which is a voltage drop along the VDD line. Therefore, when the existing power model is applied to a recent AMOLED display panel, which has a large physical size and uses a large current, power consumption cannot be accurately predicted. In this article, we propose a new model to compensate for the I-R drop and present a more accurate method for predicting AMOLED display power consumption by applying it to existing AMOLED display power models. To verify this, we conducted extensive experiments for various image databases on AMOLED display panels of Samsung Galaxy S7 and S9. When comparing the proposed display power model connected with the I-R drop model with conventional power models, it is confirmed that the proposed power model improves the accuracy by up to 70.3% over them.
Keywords: Conventional power; Display panels; Image database; Large current; Power consumed; Power model; Samsung; Voltage drop; AMOLED display; I-R drop; power model